The influence of obesity and different fat depots on adipose tissue gene expression and protein levels of cell adhesion molecules - Bošanská, L; Michalský, D; Lacinová, Z; Dostálová, I; Bártlová, M; Haluzíková, D; Matoulek, M; Kasalický, M; Haluzík, M (Physiological research, 2010)
Increased circulating adhesion molecules in patients with obesity play an important role in the development of endothelial dysfunction/atherosclerosis. The aim of this study was to assess the contribution of various fat depots to the production of adhesion molecules in obesity. 12 women with first and second degree of obesity, 13 women with third degree of obesity and 14 lean age-matched women were included into study. Circulating levels of vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), and E-selectin were measured by Luminex kits. mRNA expression of ICAM-1, VCAM-1, E-selectin, monocyte chemoattractant protein-1 (MCP-1), and CD68 in subcutaneous (SAT) and visceral adipose tissue (VAT) was measured by RT-PCR; ICAM-1 and VCAM-1 protein levels by Luminex kits, normalized to protein content. Obesity increased ICAM-1 and VCAM-1 mRNA expression and protein levels and CD68 mRNA expression in VAT. Expression of E-selectin and MCP-1 did not significantly differ between groups. Expression of ICAM-1 and VCAM-1 positively correlated with expression of CD68 in both adipose depots. In VAT, ICAM-1 and VCAM-1 expression and protein levels positively correlated with BMI. Obesity was associated with increased adhesion molecules mRNA expression and protein levels in VAT, but not in SAT. Increased adhesion molecules production in visceral fat may provide a novel direct link between visceral adiposity and increased risk of cardiovascular complications.
Keywords: index tělesné hmotnosti; messenger RNA; Up-Regulation; stupeň závažnosti nemoci; Obesity; adipozita; nitrobřišní tuk; mezibuněčná adhezivní molekula-1; upregulace; antigeny diferenciační myelomonocytární; Subcutaneous Fat, Abdominal; Middle Aged; studie případů a kontrol; Antigens, Differentiation, Myelomonocytic; Body Mass Index; Adiposity; E-Selectin; Vascular Cell Adhesion Molecule-1; Intercellular Adhesion Molecule-1; cévní buněčněadhezivní molekula-1; Cardiovascular Diseases; Chemokine CCL2; ženské pohlaví; RNA, Messenger; Humans; Intra-Abdominal Fat; biologické markery; podkožní břišní tuk; chemokin CCL2; Antigens, CD; Severity of Illness Index; lidé středního věku; obezita; E-selektin; Biomarkers; Female; molekuly buněčné adheze; CD antigeny; kardiovaskulární nemoci; lidé; Case-Control Studies; Cell Adhesion Molecules